METAPHORICAL ALLUSION IN MILITARY POLITICAL DISCOURSE - Vasylenko, Dmytro (Periodyk Naukowy Akademii Polonijnej, 2022)
The research paper is devoted to the diachronic analysis of political metaphoric allusions based on military terms in the English language. The study determines the ways of political military discourse allusions development in the 20th and at the beginning of the 21st century. The main objective of this work is to afford deeper insights into the genuine nature of metaphoric allusions, defining their forms, types and functions. The semantic and functional issues related to metaphoric allusions in the sphere of politics are the subject of the article, which has the aim of providing their interpretations, investigating their sources and use. The methods of research: empiric research, monitoring of mass media and multimedia content, classification, content analysis, semantic analysis. War words and phrases used by politicians in public addresses prone to generate new shades of meanings through military intertextual patterns and enrich the work by association thus giving it depth by revealing an implicit nature in political discourse through allusion. Its universal character has become common knowledge and ubiquitous in all walks of life. Being a figure of speech through which some counterparts are compared on the basis of their aspects to history, culture, mythology, literature, war and religion. Metaphoric allusions fill lexical gaps, characterize and deepen the understanding of the essence of existing objects.” Using war metaphoric allusions shuffles categorization in insidious ways. As such, politicians call for obedience rather than awareness and appeal to our patriotism, not to our solidarity”. (Costanza Musu , 2020: April 8). The core ideas are often taken from common sources, like war, battle, conflict which usually refer to some sort of competition, fight, or struggle and serve as a means of intertexuality in further semantic transformation in political domain acquiring a novice emotional charge.